Mechanical and Microstructural Characterization of TIG Welded Dissimilar Joints between 304L Austenitic Stainless Steel and Incoloy 800HT Nickel Alloy - Grzegorz Rogalski (Metals, 2020)
In this article, the mechanical properties and microstructure of 304L austenitic stainless steel/Incoloy 800HT dissimilar welded joints are investigated. The joints were made of 21.3 mm × 7.47 mm tubes using the TIG process with the use of S Ni 6082 nickel filler metal. No welding imperfections were found and high strength properties of joints were obtained, meeting the assumed acceptance criteria of the product’s standards. The tensile strength of the welded joints was higher than for the joined materials (Incoloy 800HT). Macro- and microscopic metallographic tests revealed the correct morphology of the joints and the appropriate structures in their critical zones. However, differences were found in the morphologies of the zones between the weld and the base materials. In fusion boundary from the side of the Incoloy 800HT alloy, no clear outline of the fusion line was observed (type A fusion boundary), while increased grain size and an epitaxial structure were observed. Inturn, in the zone: weld–304L steel, a distinct fusion line was observed with areas with an increased amount of high-temperature δ ferrite (type B fusion boundary). No precipitates were found that could reduce the resistance of the joints to intergranular corrosion. A hardness decrease (approximately 30 HV0.1) in the transition zone: austenitic steel–weld and an increase of hardness (approximately 10 HV0.1) on the opposite side of the welded joint were observed.